Immunoinflammatory Response in Critically Ill Patients: Severe Sepsis and/or Trauma. (24th November 2013) - Surbatovic, Maja; Veljovic, Milic; Jevdjic, Jasna; Popovic, Nada; Djordjevic, Dragan; Radakovic, Sonja
Abstract : Immunoinflammatory response in critically ill patients is very complex. This review explores some of the new elements of immunoinflammatory response in severe sepsis, tumor necrosis factor-alpha in severe acute pancreatitis as a clinical example of immune response in sepsis, immune response in severe trauma with or without secondary sepsis, and genetic aspects of host immuno-inflammatory response to various insults in critically ill patients.